Minimum acceptable diet and undernutrition in Bangladesh: evidence from Multiple Indicator Cluster Survey 2019 - Md Fuad Al Fidah; Md Ridwan Islam; Tahmeed Ahmed; Sharika Nuzhat (Clinical Epidemiology and Global Health, 2025)
Background: Minimum acceptable diet (MAD) remains unattainable to many children residing in low- and middle-income countries. We aimed to identify the factors influencing MAD and its association with undernutrition among Bangladeshi children aged 6–23 months. Methods: This cross-sectional study used nationally representative data from Multiple Indicator Cluster Survey, Bangladesh 2019. Total 5747 children (6–23 months) were included. Binary logistic regression models were developed to examine the association between outcome and independent variables. MAD was measured using proxy indicators, following updated WHO definitions. No causal conclusions can be drawn. Adjusted odds ratios (AOR) and their corresponding 95 % confidence intervals (CI) were reported. A p-value <0.05 was considered statistically significant. Results: The prevalence of MAD was 30.0 %. The median age (in months) of participants with adequate MAD (12.0, IQR: 16.0–20.0) was significantly (p-value<0.001) higher than their counterparts (10.0, IQR :14.0–18.0). Higher odds of attaining adequate MAD were associated with urban residents (AOR:1.45; 95 %CI:1.26–1.67), children whose mothers received secondary (AOR:1.97, 95 %CI:1.57–2.47) and post-secondary (AOR:3.80, 95 %CI:2.97–4.86) education, were exposed to media (AOR:1.64; 95 % CI:1.45–1.86) and belonged to wealthier families. However, the lower odds of achieving adequate MAD was associated significantly with mothers being primary caregivers of another child (AOR:0.72, 95 %CI:0.63–0.83). Adequate MAD was associated with lower odds of being underweight among children (AOR:0.79, 95 % CI:0.66–0.94). Conclusion: Less than one-third of Bangladeshi children aged 6–23 months achieved adequate MAD. These findings suggest the need for targeted interventions to improve complementary feeding practices, particularly in poorer and rural households, and to incorporate media in the interventions.